Sistem Pendukung Keputusan dalam Penerimaan Karyawan Menggunakan Metode Weighted Product - Albert Stephano; Renny Puspita Sari (Prosiding SISFOTEK, 2018)
In starting a business, a leader will definitely open a job vacancy for employee acceptance announced through print and social media where not just selection of employees carelessly in order to get the best employees. Mess GM which is a case study uses interviews in the selection of employees manually and criteria that have been set by the leader does not recalculate the weight obtained so that ultimately will get an employee who is not desired by the leader and have an impact on the business finances.For that we need a decision support system employee acceptance by mengguanakan method Weighted Product (WP) using multiplication to relate the rating attribute, where the rating of each attribute must first be raised with the corresponding attribute weights are called the normalization process, so mess GM get the best employees which conforms to the established criteria standards.